Prawda i fałsz wypowiedzi literackiej - Magryś, Roman (Dydaktyka Polonistyczna, 2020)
The article Truth and Falsity of Literary Statements investigates the issue of logical values,and consequently communication related status of sentences in indicative mood occurring in worksof literature. The problem is discussed with reference to theoretical assumptions of classical logic,intuitionistic logic, and other possible intensional logics as well as phenomenological concepts proposedby Roman Ingarden. In this context it is suggested that intensional systems, mainly intuitionisticlogic be adequately applied to identify logical value of literary sentences. As a result, it isassumed that the logical value of literary sentences depends on the specific logical system selected;according to the standards of intuitionistic logic, literary statements are true, likely or false. In thiscontext it seems necessary to revise Roman Ingarden’s phenomenological assumption that sentencesin indicative mood in a work of fiction do not have objective point of reference. It is suggestedthat such sentences be recognised as false, and therefore indicative of the group of their intentionalmeanings as a specific model of reality which can be deemed true or false.